MARRIAGE MIGRATION OF MONGOLIAN WOMEN TO SOUTH KOREA - Ц.Цэцэгжаргал,; EUGINA KIM, (Acta Mongolica, 2013)
Since the establishment of diplomatic relations between Mongolia and Republic of Korea (will be noted as ‘South Korea’ in this paper) in March 26th, 1990, the partnership between the two countries has been continuously developing. In company with political, diplomatic, and economic relations, Mongolia-South Korea partnerships have grown much wider and deeper in diverse socio-cultural spheres. As the two countries have advanced their relations in diverse spheres, the number of Mongolian visitors to South Korea and vice versa, South Koreans to Mongolia, has steadily increased. The Korean Ministry of Foreign Affairs announced the final total of 61,766 Mongolians and 44,360 Koreans who visited each other in 2012 (MOFA, 2013). More population mobility is expected as political, social and cultural ties of both nations are flourishing. When it comes to the volume of population movement and its growth rate, the two countries display the similar tendency. It is meaningful and desirable in a point that their relations proceed towards bilateral directions, not the unilateral one. Nevertheless, migration of Mongolian population has shown its own characteristics. First of all, Mongolian visitors are inclined to stay in South Korea relatively for a long time in comparison with South Korean visitors in Mongolia rather shorter. Next, most of Mongolian residents in South Korea (if they are legal laborers) are staying as a foreign worker under the regulation of the Employment Permit System, authorized by the South Korean Ministry of Employment and Labor.